2020
DOI: 10.1093/jbcr/iraa212
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Agreement and Reliability of Burn Size Estimations Between Emergency Physicians and Burn Unit

Abstract: The initial approach to burn injuries has remained relatively unchanged over the past several decades and revolves around trauma assessment and fluid resuscitation, frequently initiated in the emergency department (ED). While previous research suggests that emergency physicians (EP) are poor estimators at total body surface area (TBSA) affected, we believe that estimation differences are improving, specifically at academic centers with co-located burn units that emphasize burn injury education. This study inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…39 TBSA is the body surface area of burn and is one of the most important indicators to judge the severity of burn. 40 This study found that the death rate increased 1.043 times for every 1% increase in TBSA.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…39 TBSA is the body surface area of burn and is one of the most important indicators to judge the severity of burn. 40 This study found that the death rate increased 1.043 times for every 1% increase in TBSA.…”
Section: Discussionmentioning
confidence: 69%
“…Jeschke et al, found that the body surface burn area of half of the death rate of elderly patients aged 55–70 years decreased from 45% to 25%, and the analysis of burn death was linearly related to the increase of age 39 . TBSA is the body surface area of burn and is one of the most important indicators to judge the severity of burn 40 . This study found that the death rate increased 1.043 times for every 1% increase in TBSA.…”
Section: Discussionmentioning
confidence: 99%